CNKSR1 gene defect can cause syndromic autosomal recessive intellectual disability. Issue 8 (18th November 2018) - Kazeminasab, Somayeh; Taskiran, Ibrahim Ihsan; Fattahi, Zohreh; Bazazzadegan, Niloofar; Hosseini, Masoumeh; Rahimi, Maryam; Oladnabi, Morteza; Haddadi, Mohammad; Celik, Arzu; Ropers, Hans‐Hilger; Najmabadi, Hossein; Kahrizi, Kimia
Abstract : The advent of high‐throughput sequencing technologies has led to an exponential increase in the identification of novel disease‐causing genes in highly heterogeneous diseases. A novel frameshift mutation in CNKSR1 gene was detected by Next‐Generation Sequencing (NGS) in an Iranian family with syndromic autosomal recessive intellectual disability (ARID). CNKSR1 encodes a connector enhancer of kinase suppressor of Ras 1, which acts as a scaffold component for receptor tyrosine kinase in mitogen‐activated protein kinase (MAPK) cascades. CNKSR1 interacts with proteins which have already been shown to be associated with intellectual disability (ID) in the MAPK signaling pathway and promotes cell migration through RhoA‐mediated c‐Jun N‐terminal kinase (JNK) activation. Lack of CNKSR1 transcripts and protein was observed in lymphoblastoid cells derived from affected patients using qRT–PCR and western blot analysis, respectively. Furthermore, RNAi‐mediated knockdown of cnk, the CNKSR1 orthologue in Drosophila melanogaster brain, led to defects in eye and mushroom body (MB) structures. In conclusion, our findings support the possible role of CNKSR1 in brain development which can lead to cognitive impairment.